Signifikansi Studi Biblika Kontekstual dalam Kehidupan Iman Kristen di Era Disruptif - Jefri Andri Saputra; Sanda Sanda; Asari Asari; Yiska Leban; Yunira Yanti (Sekolah Tinggi Teologi Berita Hidup, 2022)
Biblical's study is an urgent need to bridge the context of the scriptures and the context of the church today. This issue is difficult when the church faces a disruptive era. This era creates a lot of irrelevance and requires constant change. Through a descriptive approach, the writer reviewed the significance of the biblical -contextual study in the disruptive era. At the end of this article, the author found that the biblical-contextual study could serve as a guide in responding to the disruptions of information particularly theological issues, formulating Christian ethical concepts, and anthropological adaptation. The author hope that this article will encourage church people to study the bible in the disruptive era.